2018
DOI: 10.1108/jocm-01-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life of Emirati women and its influence on job satisfaction and turnover intention

Abstract: Purpose The purpose of the paper is to examine the quality of work life (QoWL) and its influence on job satisfaction and turnover (job-leaving) intention of Emirati women employed in various public sector organizations in the United Arab Emirates (UAE). Design/methodology/approach Data were collected through a structured questionnaire gleaned from literature, and were analyzed through partial least squares structural equation modeling. Findings QoWL was found to have a significant relationship with all var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
107
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 62 publications
22
107
0
6
Order By: Relevance
“…Stress is present in all forms of jobs, but its intensity varies (Nguyen et al, 2017). Recognition in terms of monetary or non-monetary benefits for work well performed by the employee boosts confidence of the employee, benefiting himself as well as the organization (Jabeen et al, 2018). According to Hale and Maehling (1993), recognition is a valuable tool of management and gets translated into time, money and personal commitment to the program.…”
Section: Implication and Contribution For Practicementioning
confidence: 99%
“…Stress is present in all forms of jobs, but its intensity varies (Nguyen et al, 2017). Recognition in terms of monetary or non-monetary benefits for work well performed by the employee boosts confidence of the employee, benefiting himself as well as the organization (Jabeen et al, 2018). According to Hale and Maehling (1993), recognition is a valuable tool of management and gets translated into time, money and personal commitment to the program.…”
Section: Implication and Contribution For Practicementioning
confidence: 99%
“…QWL affected negatively the burnout [6]. [31] found that quality of working life is a predictor of TI among women working in UAE. The mediating role of QWL was found significant in the study of [10] who found that QWL affected negatively the TI and mediated the effect of supervisor support with organizational commitment, life satisfaction and TI.…”
Section: E Mediating Role Of Quality Of Working Lifementioning
confidence: 99%
“…QWL is defined as employees' perceptions of employees' physical and mental well-being [30]. It is different from job satisfaction because it concerns not only the work but the balance between work and life, which include family, outdoor activities and leisure [31]. QWL was found to be studied by few studies.…”
Section: E Mediating Role Of Quality Of Working Lifementioning
confidence: 99%
“…Various studies showed that the SIJS presents good reliability, namely, internal consistency estimates [52][53][54][55]. Hypothesis 2 assumes that the SIJS presents adequate evidence validity in terms of reliability of the scores.…”
Section: Introductionmentioning
confidence: 97%